2006
DOI: 10.1142/s0218348x0600312x
|View full text |Cite
|
Sign up to set email alerts
|

Multifractal Measures on Small-World Networks

Abstract: We investigate the multifractals of the normalized first passage time on one-dimensional small-world network with both reflecting and absorbing barriers. The multifractals is estimated from the distribution of the normalized first passage time characterized by the random walk on the small-world network with three fractions of edges rewired randomly. Particularly, our estimate is the fractal dimension D 0 = 0. 917, 0.926, 0.930 for lattice points L = 80 and a randomly rewired fraction p = 0.2. The numerical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The existing body of work has demonstrated that randomness increases fractal dimension, d f , reduces average shortest path length, l, and suppresses local clustering. 25,80,[86][87][88][89][90][91][92][93][94] Consequently, the size-matched random ER and BR networks have values of d f higher by 0.6 to 1.1 units and values of C 4 smaller by one to three orders of magnitude in comparison to the RNs. BR networks show higher local clustering but are still much less ordered than RNs.…”
Section: Comparisons To Generative Network Modelsmentioning
confidence: 96%
See 1 more Smart Citation
“…The existing body of work has demonstrated that randomness increases fractal dimension, d f , reduces average shortest path length, l, and suppresses local clustering. 25,80,[86][87][88][89][90][91][92][93][94] Consequently, the size-matched random ER and BR networks have values of d f higher by 0.6 to 1.1 units and values of C 4 smaller by one to three orders of magnitude in comparison to the RNs. BR networks show higher local clustering but are still much less ordered than RNs.…”
Section: Comparisons To Generative Network Modelsmentioning
confidence: 96%
“…90,91 Figure4shows the comparison of the average shortest path length, l (metric property), the average square clustering coefficient, C 4 (local property), and the fractal dimension,d f ,between three size classes of RNs: small (C 2 H 5 NO 2 , CH 19 NO 9 , and C 2 H 10 O 5 ), medium (C 3 H 6 O 3 , C 2 H 6 N 2 O 2 , and C 2 H 18 O 9 ), and large (C 3 H 8 O 4 , C 3 H 4 N 2 O, C 2 H 8 N 2 O 3 , and C 3 H 5 NO 2 )…”
mentioning
confidence: 99%
“…The main issues on deterministic networks include network modeling, 7 random walks, [8][9][10] calculations of Laplacian eigenvalues, 11 and enumeration of spanning trees. 12 Among them, obtaining an exact formula for enumeration of spanning trees is challenging due to the complexity and diversity of networks.…”
Section: Introductionmentioning
confidence: 99%